Explaining Indonesian Local Government Performance in Handling Natural Crisis: Local Politics and Government Capacity - Adfin Rochmad Baidhowah; Andi Pitono (ARRUS Journal of Social Sciences and Humanities, 2026)
By 2024, more than sixty percent of local governments in Indonesia were classified as high-risk for natural disasters, with none in the low-risk category. However, the level of local governments resilience to natural threats shows significant differences across regions. This study aims to examine the extent to which decentralization—as measured by indicators of local democracy and capacity—influences the resilience performance of local governments in facing natural crises. Using Ordinary Least Squares regression analysis across all Indonesian local governments, the results show that the higher the level of fraud in the election process of regional heads, the lower the level of resilience of local governments to natural crises. Regional heads serving in their second terms also tend to have lower levels of resilience than those in their first terms. Conversely, increasing fiscal capacity through larger regional budgets and improving bureaucratic reform contribute positively to increasing local government resilience. Therefore, strengthening budget governance and deepening bureaucratic reform are key strategies to mitigate the negative impact of undemocratic political behavior and second terms of regional heads on local government resilience in facing natural crises. If budget capacity is also low under the above conditions, strengthening bureaucratic reform is the key.